Cleaning business gets new owners (Raton, NM Raton Range, 1994)
This article is about the sale of Zeller's Cleaners.
Newspaper article
Master list item #: 68
File location is in the Raton file Cabinet
Keywords: Belcheff, Steve; Belcheff, Alba; Feerer, Jim; Feerer, Alice; Bacca, Mary; Zeller's Cleaners; Apparel Cleaning Businesses; Dry Cleaning; Local Business; Owner History; 128 South Second; 401 S. Second Street -- 1970; Raton, New Mexico